Digitalization of customer service in small and medium-sized enterprises: drivers for the development and improvement - Costa, Ana Carolina Ferreira [UNESP] (2024)
Purpose: Small and medium-sized enterprises (SMEs) are fundamental to the socioeconomic development of a country or region. They directly contribute to increasing employment generation and improving income distribution. Despite the importance of SMEs, there are still opportunities for developing works that support and guide SMEs to use digital technologies, especially to digitalize their customer service. Therefore, this work aims to propose drivers containing recommendations for developing and improving the digitalization of customer service in SMEs. Design/methodology/approach: This work uses a qualitative approach to systematize the main SMEs' characteristics and identify the boosting elements of the digitalization of customer service in the scientific literature. To this end, the authors conducted a content analysis of the most influential empirical and theoretical articles on the theme published from 2016 to 2021 in the Scopus database. Findings: This work identified 38 boosting elements of the digitalization of customer service based on the scientific literature. These elements were grouped into six drivers for developing and improving the digitalization of customer service. The drivers contain recommendations that were adapted for SMEs according to their characteristics and based on the experience of the authors of this work. Originality/value: This work contributes to promoting socioeconomic development, providing important solutions for managers and owners of SMEs to improve their customer service. The proposed drivers support and encourage the use of digital technologies for developing and improving customer service, overcoming the challenges of digitalization in these companies. Thus, SMEs will be able to increase the satisfaction of their customers and improve their competitiveness.